Влияние некоторых компонентов растительного сока на активность пищеварительных ферментов клещей Tetranychus cinnabarinus Boisd - Акимов, И.А.; Барабанова, В.В. (Вестник зоологии, 1977)
It is determined that ions of chlorine, NO₃, glutamine and bean leaves extracts activate digestive enzymes of T. cinnabarinus B o i s d u v a l. Glutamine is most effective for the activation. The substances under test not only activate enzymes of T. cinnabarinus but also expand the range of action for some of them.